2019
DOI: 10.1107/s205698901900999x
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structures of {LnCu5}3+ (Ln = Gd, Dy and Ho) 15-metallacrown-5 complexes and a reevaluation of the isotypic EuIII analogue

Abstract: Three new isotypic heteropolynuclear complexes, namely pentaaquacarbonatopentakis(glycinehydroxamato)nitratopentacopper(II)lanthanide(III) x-hydrate, [LnCu5(GlyHA)5(CO3)(NO3)(H2O)5]·xH2O (GlyHA2− is glycinehydroxamate, N-hydroxyglycinamidate or aminoacetohydroxamate, C2H4N2O2 2−), with lanthanide(III) (Ln III) = gadolinium (Gd, 1, x = 3.5), dysprosium (Dy, 2, x = 3.28) and holmium (Ho, 3, x = 3.445), within a 15-metallacrown-5 class were obtained on reaction of lanthanide(II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…The structure of the 15-metallacrown-5 fragments [GdCu 5 (GlyHA) 5 ] 3 + in complex 1 (Figure 2) is similar to that of several previously reported glycinehydroxamate Ln(III)-Cu(II) 15-metallacrowns-5, [52,53,[70][71][72] and discussion of structural features of 1 will thus be limited to supramolecular interactions of the [GdCu 5 (GlyHA) 5 ] 3 + cation with anions, sodium cations, and their solvating molecules. Details of the structural features of the metallamacrocyclic core {GdCu 5 } 3 + itself are given in the Supplementary Information section.…”
Section: General Structural Description Ofsupporting
confidence: 83%
See 2 more Smart Citations
“…The structure of the 15-metallacrown-5 fragments [GdCu 5 (GlyHA) 5 ] 3 + in complex 1 (Figure 2) is similar to that of several previously reported glycinehydroxamate Ln(III)-Cu(II) 15-metallacrowns-5, [52,53,[70][71][72] and discussion of structural features of 1 will thus be limited to supramolecular interactions of the [GdCu 5 (GlyHA) 5 ] 3 + cation with anions, sodium cations, and their solvating molecules. Details of the structural features of the metallamacrocyclic core {GdCu 5 } 3 + itself are given in the Supplementary Information section.…”
Section: General Structural Description Ofsupporting
confidence: 83%
“…Substitution of anions in [GdCu 5 (GlyHA) 5 (CO 3 )(NO 3 )(H 2 O) 5 ] • 3.5H 2 O [52,53] by metathesis with an excess of the disulfonate linker Na 2 L (L 2À is 4,4'-bis(2sulfonatostyryl)biphenyl, Scheme 1) was carried out in a DMFwater solution and led to the formation of the centrosymmetric complex 1, {Na 2 (H 2 O) 8 [GdCu 5 (GlyHA) 5 (H 2 O) 4 L] 2 }L 2 • 2.5DMF…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…these complexes feature, similar to 1, individual molecular complex cations (Katkova et al, 2015a,b;Pavlishchuk et al, 2011Pavlishchuk et al, , 2017aPavlishchuk et al, , 2018Pavlishchuk et al, , 2019Stemmler et al, 1999;Muravyeva et al, 2016;Kremlev et al, 2016), but a small number of oligomerized examples have also been reported (Pavlishchuk et al, 2017a(Pavlishchuk et al, , 2018.…”
Section: Database Surveymentioning
confidence: 71%
“…Numerous research studies devoted to polynuclear 3d-4f assemblies have been stimulated by their non-trivial luminescence properties (Jankolovits et al, 2011;Maity et al, 2015), single-molecule magnet (SMM) behaviour (Dhers et al, 2016;Zangana et al, 2014) and their significant magnetocaloric effect (Pavlishchuk & Pavlishchuk, 2020;Zheng et al, 2014). The 15-metallacrown-5 complexes are 3d-4f metallamacrocyclic assemblies, which can be easily obtained from one-step reactions between an -substituted hydroxamic acid and the corresponding salts of transition metals and lanthanides (Stemmler et al, 1999;Pavlishchuk et al, 2011Pavlishchuk et al, , 2019. Compounds bearing 15-metallacrown-5 {LnCu 5 } 3+ units have demonstrated the ability to serve as sensors (Zabrodina et al, 2018), can absorb and adsorb various small molecules (Lim et al, 2010;Pavlishchuk et al, 2014;Ostrowska et al, 2016) and display SMM behaviour (Wang et al, 2019(Wang et al, , 2021Zaleski et al, 2006;Wu et al, 2021).…”
Section: Chemical Contextmentioning
confidence: 99%